ORNAMEN DAN PERKEMBANGANNYA PADA PEMBUATAN SENI KERAJINAN TATAH SUNGGING KULIT DI WUKIRSARI, BANTUL, YOGYAKARTA - Ibnu Banuhali; Rofiatun Nafiah (Politeknik ATK Yogyakarta, 2013)
This research wants to study why ornaments in leather puppets reflected in their body shape, clothing, and accessories are still interesting for craftsmen as their inspiration in creating various products. This research also studies about aesthetic structure, motives or ornament styles, and also ornaments roles in improving the art performance quality of leather carving and coloring. This research employs library, observation and interview methods in order to collect the data. Since the data were gained qualitatively, so this research analyzed them using descriptive qualitative method.The results of the research show that ornamentation of various kinds of leather carving products by the craftsmen in Pucung, Wukirsari, Imogiri is still the continuation of leather puppet making tradition from the ancestors. Although they have already made product varieties, but the ornaments in leather puppets and their making techniques still strongly influence the works resulted. This is due to several factors: 1. the motivation to preserve the carving tradition; 2. strong influence of puppets making procedures, 3. craft products demanded by consumers; 4. outside influences such as the use of synthetic colors which further improves the quality of appearance and attractiveness.